2007
DOI: 10.1111/j.1365-2893.2006.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulators, sFas and Fas‐L as potential noninvasive predictors of IFN treatment in patients with HCV genotype‐4

Abstract: Recent studies have indicated that cytokines can be used as markers for disease progression in hepatitis C virus (HCV)-infected patients, therefore this study was conducted to determine the influence of pegylated IFN vs standard IFN on interleukin-2 receptor (IL-2R), IL-6R, IL-8, TNFR-I, TNFR-II, sFas, and sFas-L in Egyptian patients with chronic hepatitis C genotype 4, as no previous studies have been performed on this genotype. We also aim at establishing a possible relationship between these cytokines and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
4
9
2
2
Order By: Relevance
“…The differences noticed might be due to the fact that their patients had compensated liver diseases; unlike ours. This figure, however, was in agreement with that in our previous study [26]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The differences noticed might be due to the fact that their patients had compensated liver diseases; unlike ours. This figure, however, was in agreement with that in our previous study [26]. …”
Section: Discussionsupporting
confidence: 94%
“…This was in contrast with the study of Fargion et al [28] in which no significant association with response was found with sex or age. Also our previous study showed that six out of 9 (67%) females treated with standard interferon had sustained viral response, whereas only one of 5 females treated with pegylated interferon showed viral response [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Eighty-four studies were closely evaluated for eligibility[1016, 18, 26101]. Fourteen studies did not have extractable treatment outcomes data[26, 29, 36, 47, 50, 58, 61, 64, 74, 86, 87, 92, 100, 101]. Six were redundant[49, 51, 57, 68, 89, 99] and four were not relevant[30, 43, 60, 94].…”
Section: Resultsmentioning
confidence: 99%
“…Например, пока-зано, что у пациентов с циррозом печени хоро-ший прогноз относительно смертности связан с повышенным содержанием в плазме рас-творимых TNFRII-рецепторов [Grunhage et al, 2008]. Содержание растворимых TNFR может быть использовано также как маркер эффек-тивности лечения иммунномодулирующими препаратами пациентов с заболеваниями пе-чени, в частности вирусным гепатитом С [Zekri et al, 2007]. Однако связан ли повышенный уровень этих рецепторов с тяжестью НАЖБП, пока не ясно.…”
Section: рецепторы Tnfα и Il6unclassified